Case presentation – unilateral dyskinetic cerebral palsy: time for a change in cerebral palsy classification? (One Health & Risk Management, 2024)
Introduction. Unilateral dyskinesia is a rare neurological disorder characterized by involuntary, abnormal movements on one side of the body. In children, understanding its clinical presentation and age-appropriate rehabilitation strategies is essential for the best outcome. Material and methods. In this case-presentation, we conducted an in-depth examination of a 10-year-old boy with unilateral dyskinesia, previously diagnosed with bilateral spastic cerebral palsy. Extensive pediatric neurological assessments, including neuroimaging and child-friendly clinical evaluations, were performed to comprehensively document the patient's condition. Results. Birth data: 39 weeks gestation, singleton, weight – 3950 g, length – 56 cm, head circumference – 36 cm, Apgar score at 5 minutes – 7, without birth-related complications. Paraclinical investigations revealed MRI-identified basal ganglia lesions in the putamen. Functional classifications indicated GMFCS II, MACS II, epilepsy, normal vision, normal hearing, EDACS level I, Viking speech scale III, and moderate intellectual disability. The pediatric patient exhibited pronounced dyskinesia limited to the right side of the body, which has progressively worsened over the past six years.Conclusions. The results are in line with specific variables of dyskinetic CP. This study emphasizes the challenges in diagnosing pediatric patients with unilateral dyskinesia during the early stages. Clinical features are evident; therefore, rehabilitation strategies should be selected accordingly.
Keywords: dyskinesia; unilateral; case study; rehabilitation